Intertidal macro echinoderm diversity in Can Apog Reef, Biasong, San Isidro, Leyte, Philippines - Perino, Armand Joseph E. (Armand Joseph E. Perino, 2014)
The study was conducted on the intertidal zone of Can Apog reef, Biasong, San Isidro, Leyte, Philippines to determine the presence and abundance of echinoderms in the area in space and time. Using six 500 meter square (100 m x 5 m) permanent belt transects, 22 species of echinoderms were observed during the monthly surveys from October 2013 to February 2014 in depths ranging from 1 m to 3.3 m. Species found represented the classes of Ophiuroidea, Holothuroidea, Asteroidea, and Echinoidea. The ophiuroid Macrophiothrix longipeda was the most abundant (28.1%), while the holothuroid Actinopyga echinites was the least abundant (0.03%). There is no consistent trend upon the effects of space and time to the echinoderm diversity. Spatial inconsistency was due to unpredictable natural phenomena that effect diversity from time to time. Effect of time was also inconsistent because it generally needs a long time to establish a stable trend. Because of this, it is recommended for future surveys to have a longer duration and a wider area scope.